2010
DOI: 10.1029/2008wr007595
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and characterization of solute transport during two tracer tests in a shallow aquifer using electrical resistivity tomography and multilevel groundwater samplers

Abstract: [1] The relevance of aquifer heterogeneity for flow and transport is recognized broadly; however, its characterization is hampered by the inaccessibility of the subsurface. Time-lapse electrical resistivity tomography (ERT) offers the possibility of imaging noninvasively subsurface transport. We present results of two tracer tests that were carried out successively in a shallow aquifer at the Krauthausen test site (Germany). The breakthroughs of an electrically conductive and a resistive tracer were monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
94
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 57 publications
1
94
0
Order By: Relevance
“…In the past two decades, ERT has been used to monitor salt tracer tests or water infiltration through the vadose zone in relatively homogeneous or stratified hydrogeological systems either in the laboratory (Binley et al, 1996a;Slater et al, , 2002Koestel et al, 2008) or in test sites (Slater et al, 1997a;al Hagrey and Michaelsen, 1999;Day-Lewis et al, 2003;Singha and Gorelick, 2005;Cassiani et al, 2006;Müller et al, 2010). Table 1 presents a nonexhaustive list of surveys that were designed to monitor water infiltration or salt tracer propagation in the laboratory and in the field.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, ERT has been used to monitor salt tracer tests or water infiltration through the vadose zone in relatively homogeneous or stratified hydrogeological systems either in the laboratory (Binley et al, 1996a;Slater et al, , 2002Koestel et al, 2008) or in test sites (Slater et al, 1997a;al Hagrey and Michaelsen, 1999;Day-Lewis et al, 2003;Singha and Gorelick, 2005;Cassiani et al, 2006;Müller et al, 2010). Table 1 presents a nonexhaustive list of surveys that were designed to monitor water infiltration or salt tracer propagation in the laboratory and in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Multilevel sampling (MLS) has been found useful for improving hydrochemical and hydraulic characterizations of aquifers relative to other sampling methods (Ronen et al, 1986;Cherry et al, 2007;Müller et al, 2010;. Depth-dependent samples from deep aquifers are usually obtained during drilling (Williams and Chou, 2007;Hendry et al, 2011); hence interpretation of aquifer dynamics from these single-time data sets is limited.…”
Section: Introductionmentioning
confidence: 99%
“…ERT proved its ability to detect temperature changes below 1.5 °C and then to follow lower incremental changes. The design of cross-borehole experiment allows more flexibility regarding the depth of the reservoir and the resolution since a major drawback of surface ERT is the loss of resolution/sensitivity with increasing depth [51,107]. Firmbach et al [108] studied heat transport with ERT in an experimental box (1 m × 0.4 m × 0.4 m) with various levels of saturation.…”
Section: Using Ert To Monitor Temperature Changesmentioning
confidence: 99%
“…However, plenty of studies showed the ability of ERT in general to follow dynamic processes in less favourable conditions. As an example, Kemna et al [50] and then Müller et al [107] successfully used ERT in the Krauthausen test site in Germany to follow different types of tracer migration within a 10m thick heterogeneous and layered sandy aquifer. Supper et al [109] demonstrated the ability of the method to study seasonal variations in permafrost.…”
Section: Using Ert To Monitor Temperature Changesmentioning
confidence: 99%